2017
DOI: 10.1155/2017/7074147
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effects of Bioactive Constituents from Chinese Propolis against Acute Oxidative Stress Induced by Hydrogen Peroxide in Cardiac H9c2 Cells

Abstract: Chinese propolis (CP) is known as a health food but its beneficial effects in protecting cardiomyocytes remain elusive. Here, we investigated the effects of CP and its active compounds on hydrogen peroxide (H2O2) induced rats cardiomyocytes (H9c2) oxidative injury. Cell viability decreases induced by H2O2 were mitigated by different CP extracts using various solvents. From these active fractions, six active compounds were separated and identified. Among tested isolated compound, the cytoprotective activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Finally, the fractions eluted with 40%, 50%, 60%, 65%, 70%, 75%, 80%, and 90% methanol-water solution gave subfractionI, II, III, IV, V, VI, VII and VII, respectively. The chemical constituents of eight subfractions were analyzed by HPLC-DAD/Q-TOF-MS analysis as previously described [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the fractions eluted with 40%, 50%, 60%, 65%, 70%, 75%, 80%, and 90% methanol-water solution gave subfractionI, II, III, IV, V, VI, VII and VII, respectively. The chemical constituents of eight subfractions were analyzed by HPLC-DAD/Q-TOF-MS analysis as previously described [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies indicate that caffeic acid (CA), and its phenethyl ester (CAPE) are compounds with potent chemopreventive effects, inter alia by cell cycle inhibition and proapoptotic action [ 13 , 14 , 15 , 16 ]. CAPE is a polyphenol which is a component of honeybee propolis.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [53] have reported similar findings regarding the protective properties of CAPE against H 2 O 2 -induced death using the LDH assay in 661W mouse cells, i.e., CAPE influences inhibition of cell death in a dose-dependent manner. Sun et al [54] used rat cardiomyocytes cells to follow the action of 2 mM H 2 O 2 ; CAPE was protective, increasing the lifespan of the cells under oxidative stress. The antioxidant properties of CAPE have also been confirmed by Chen et al [55], who found that in peripheral blood mononuclear cells CAPE inhibits xanthine oxidase, which, under physiological conditions, is the source of superoxide anions with the ability to inhibit lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%